Do Management Actions to Restore Rare Habitat Benefit Native Fish Conservation? Distribution of Juvenile Native Fish Among Shoreline Habitats of the Colorado River. (8th October 2014) - Dodrill, M. J.; Yackulic, C. B.; Gerig, B.; Pine, W. E.; Korman, J.; Finch, C.
Abstract: Many management actions in aquatic ecosystems are directed at restoring or improving specific habitats to benefit fish populations. In the Grand Canyon reach of the Colorado River, experimental flow operations as part of the Glen Canyon Dam Adaptive Management Program have been designed to restore sandbars and associated backwater habitats. Backwaters can have warmer water temperatures than other habitats, and native fish, including the federally endangered humpback chub Gila cypha, are frequently observed in backwaters, leading to a common perception that this habitat is critical for juvenile native fish conservation. However, it is unknown how fish densities in backwaters compare with that in other habitats or what proportion of juvenile fish populations reside in backwaters. Here, we develop and fit multi‐species hierarchical models to estimate habitat‐specific abundances and densities of juvenile humpback chub, bluehead sucker Catostomus discobolus, flannelmouth sucker Catostomus latipinnis and speckled dace Rhinichthys osculus in a portion of the Colorado River. Densities of all four native fish were greatest in backwater habitats in 2009 and 2010. However, backwaters are rare and ephemeral habitats, so they contain only a small portion of the overall population. For example, the total abundance of juvenile humpback chub in this study was much higher in talus than in backwater habitats. Moreover, when we extrapolated relative densities based on estimates of backwater prevalence directly after a controlled flood, the majority of juvenile humpback chub were still found outside of backwaters. This suggests that the role of controlled floods in influencing native fish population trends may be limited in this section of the Colorado River. Copyright © 2014 John Wiley & Sons, Ltd.